Malawi : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Malawi. (IMF Staff Country Reports; Country Report, 2021)
Malawi, a fragile state with one of the highest incidences of poverty, food insecurity and frequent weather-related shocks, has been severely affected by the pandemic. There are signs of gradual recovery and daily COVID-19 positive cases remain relatively low: real GDP growth in 2021 is projected to pick up to 2.2 percent from 0.9 percent in 2020 helped by a good harvest. However, inflation is expected to increase to 9 percent in 2021 from 8.6 percent in 2020, driven by increases in prices of fuel, fertilizer and food, leaving real per capita growth in the negative region.